Dampak Pandemi Covid-19 Terhadap Masyarakat di Kampung Tarekat Naqsabandiyah Babussalam Besilam - Taufiqurrahman, Taufiqurrahman; Hartanto, Deni; Fadli, Muhammad (Medan Resource Center, 2023)
Kampung Tarekat Naqsabandiyah Babussalam in Langkat was founded by Syekh Abdul Wahab Rokan upon the initiative of Sultan Musa. This village, built and developed with a spirit of mutual cooperation, is exceptional as it was established as a center for teaching and spreading the Naqsabandiyah Sufi Order, which played a vital role in disseminating this spiritual path. The purpose of this writing is to understand the impact of the COVID-19 pandemic on the behavior of the community around Kampung Tarekat Naqsabandiyah Babussalam in Besilam. The research method employs both primary and secondary data obtained from the Central Bureau of Statistics (Badan Pusat Statistik) of Langkat Regency. The findings of this research indicate that a majority of the community experienced changes in both the economic and behavioral sectors. Economically, the income of the community decreased due to the decline in businesses around the religious tourism area. Regarding behavior, the community adhered to government advisories such as working from home (WFH), maintaining distance, wearing double-layered masks, and consistently using hand sanitizer when traveling.